Vertebral artery transection with pseudoaneurysm and arteriovenous fistula requiring antegrade and retrograde embolization - Maham Karatela, BA; E. Hope Weissler, MD; Mitchell W. Cox, MD; Zachary F. Williams, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2022)
Traumatic vertebral artery injury is a rare, life-threatening injury that has been increasingly managed with endovascular intervention. However, an antegrade endovascular approach alone can fail to occlude traumatic pseudoaneurysms (PSAs) and arteriovenous fistulas (AVFs), requiring high-risk surgical reoperation. We have presented the case of a 27-year-old man with traumatic right vertebral artery PSA and AVF. Despite successful ipsilateral coil embolization, the PSA and AVF persisted via retrograde filling from the contralateral vertebral artery. Distal coil embolization was achieved through the contralateral vertebral artery in a novel “up and over” approach through the basilar artery. The findings from our case report have broadened the endovascular options for complicated traumatic injuries.